Gold glyconanoparticles coupled to listeriolysin O 91–99 peptide serve as adjuvant therapy against melanoma. Issue 30 (17th July 2017) - Calderon-Gonzalez, R.; Terán-Navarro, H.; García, I.; Marradi, M.; Salcines-Cuevas, D.; Yañez-Diaz, S.; Solis-Angulo, A.; Frande-Cabanes, E.; Fariñas, M. C.; Garcia-Castaño, A.; Gomez-Roman, J.; Penades, S.; et al.
Abstract : Dendritic cell-based (DC-based) vaccines are promising immunotherapies for cancer. Abstract : Dendritic cell-based (DC-based) vaccines are promising immunotherapies for cancer. However, several factors, such as the lack of efficient targeted delivery and the sources and types of DCs, have limited the efficacy of DCs and their clinical potential. We propose an alternative nanotechnology-based vaccine platform with antibacterial prophylactic abilities that uses gold glyconanoparticles coupled to listeriolysin O 91–99 peptide (GNP-LLO91–99 ), which acts as a novel adjuvant for cancer therapy. GNP-LLO91–99, when used to vaccinate mice, exhibited dual antitumour activities, namely, the inhibition of tumour migration and growth and adjuvant activity for recruiting and activating DCs, including those from melanoma patients. GNP-LLO91–99 nanoparticles caused tumour apoptosis and induced antigen- and melanoma-specific cytotoxic Th1 responses ( P ≤ 0.5). We propose this adjuvant nanotherapy for preventing the progression of the first stages of melanoma.